Translating personality into landscape Frank Kraushaar - Kraushaar, Frank (Acta Orientalia Vilnensia, 2007)
This essay stems from a hypothesis which belongs to a work in progress: an attempt to understand and to make translatable into contemporary conceptions the figure of the anonymous 隱者 (yin zhe) and its formation into a kind of humanistic cipher or an empty interior space sketched like a human being in classical Chinese poetry and Tang and Song painting. The idea is that the correspondence of personality and landscape in Chinese aesthetics replaces its Western counterpart―the relativity of subjectivity and outer space. The first part of the essay delineates differences in the approach to landscape or 山水 (shan-shui) and emphasizes that the appreciation of both essentially changes as soon as the cultural information does, which makes similarities of certain approaches―as in romantic landscapes and Chinese shan-shui―deluding rather than coherent. The last part focuses on a detail in the construction of the shan-shui in relation to concepts of personality which I call distance and framing. This combination of an absolute spatial order obtained by distance and its microcosmical, individual correspondence in a personally shaped frame seems the characteristic Chinese way to translate concepts of personality into an aesthetic reality―almost bare of any relation to the physical presence of the subject.